Upaya Penurunan Kejadian Stunting Pada Masa Pandemi di Indonesia - Ahmad Aryo Wibowo; Defitria Nabilla; Natasha Putri Ayu Kayla; Bella Aprilia Zahra; Tirza Grenluisa; Chahya Kharin Herbawani (STIKes Karsa Husada Garut, 2022)
The Prevalence of stunting in Indonesia in 2017 was quite large, around 29.6%. Stunting has an impact on the disruption of intellectual and cognitive abilities, and is susceptible to degenerative diseases, thereby reducing quality human resources. Especially during the Covid-19 pandemic, stunting prevention activities had to be stopped to prevent the virus to spread. This literature review aims to examine the efforts that can be made to reduce the prevalence of stunting during the pandemic. This literature review uses 3 databases, namely Google Scholar, Garuda, and PubMed. This literature is limited by inclusion and exclusion criteria. The inclusion criteria used in selecting the literature were published between 2020 and 2022, focusing on efforts to reduce stunting during the pandemic and full text, and original research. Based on 8 journals there are 9 efforts that can be done, namely education on balanced nutrition, stunting literacy, pregnant women classes, mobile edu app-based education, e-books for cadre education, health counseling, measuring nutritional status and toddler’s health, providing healthy and nutritious food, as well as stunting campaigns through influencers.